If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 6 = 5y + -9 Reorder the terms: 6 + 6y = 5y + -9 Reorder the terms: 6 + 6y = -9 + 5y Solving 6 + 6y = -9 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 6 + 6y + -5y = -9 + 5y + -5y Combine like terms: 6y + -5y = 1y 6 + 1y = -9 + 5y + -5y Combine like terms: 5y + -5y = 0 6 + 1y = -9 + 0 6 + 1y = -9 Add '-6' to each side of the equation. 6 + -6 + 1y = -9 + -6 Combine like terms: 6 + -6 = 0 0 + 1y = -9 + -6 1y = -9 + -6 Combine like terms: -9 + -6 = -15 1y = -15 Divide each side by '1'. y = -15 Simplifying y = -15
| 26=(-7x)-2 | | x(2)+18x+81=0 | | 6z^2-7z-10= | | 40x+80=0 | | 5(x-5)-8=-6(-2v+7)-x | | 10x+3y=-30 | | 2*sin(7x)=1 | | 0.09x^2-bx+4=0 | | 6(5s-13)-12(2s+9)=0 | | 0=-16t^2+128t+4 | | -(4x-4)-(6x-3)+6=-9(x-5)-(8x+8)+9 | | x^2+42+360=0 | | 8.50t=255.00 | | 8.50t=225.00 | | -5a-8a+15a-3=15 | | 88-7x=23 | | 8.50t=229.50 | | -4(5+x)+x+6=x | | 2+1.25x=16-1.5x | | 2(x-1)+3=2x-7 | | 3(2+X)=32 | | 4x^6+36x^5+80x^4=0 | | 21j-16j+3=18 | | -9x-4y=17 | | 9(3x-9)-7-2x=x | | 4=3x+31 | | 7(2x+9)+6=14x+69 | | X=7-2t*t | | 10x-12y=14 | | ln(5x+3)=0 | | 9x+2=7x+12 | | 2t^5-14t^4+20t^3=0 |